Nutritional Status and Basic Hygiene Practices of Rural School Age Children of Savar Region, Dhaka, Bangladesh - Sahadat Hossain; Fahad Ahmed; Shakhaoat Hossain; Tajuddin Sikder (University Library System, University of Pittsburgh, 2018)
Introduction: School children in the  developing countries are susceptible to nutrition related health problems due to demographic and socio-economic factors, as well as limited access to food. Since BMI is a common proxy measure used to evaluate nutritional status, the aim of this study was to investigate the BMI categories in school-aged children in Dhaka, Bangladesh. Methods: A cross sectional study of 155 children, aged 6-12 years was conducted at Jahangirnagar University School in Dhaka, Bangladesh. The data collection was performed by in-person interviews and semi-structured questionnaires. Descriptive statistics, χ2 test, Fisher's exact test, and One-Way ANOVA test were performed to compare the variables based on BMI percentiles. Data were analyzed using the Microsoft Excel program (version 2010). Results: Mean BMI of the students was 17.27 (SD=3.16). The prevalence of underweight and overweight/obesity was 11.0% and 25.8%, respectively. Categories of BMI percentiles were associated with birth order (p=0.026), personal hygiene practices (washing hands after coming home from outside (p<0.001) and before meal (p=0.045)), brushing teeth (p<0.001), the number of food items consumed daily (p<0.001), and mothers' occupation (p=0.006). In context of basic hygiene practice, 61.3 % of respondents washed hands after coming home from outside, and 93.5 % reported washing hands before the meals. Conclusions: This study revealed that more than one third of the students had abnormal BMI. BMI screening in rural schools needs to be recommended in early grades for all children.